Neural conduction impairment of the auditory brainstem in babies with bronchopulmonary dysplasia while being diagnosed - Ze Dong Jiang; Rong Yin; James Ken Jiang; Cui Wang (Scientific Reports)
Abstract Brainstem neural conduction was investigated in 78 very low birthweight (VLBW) at 36 weeks of postconceptional age while diagnosing neonatal bronchopulmonary dysplasia (BPD). The maximum length sequence technique was used to study brainstem auditory evoked response (MLS BAER). Compared with healthy controls, VLBW babies diagnosed with BPD manifested significant prolongation of wave V latency and I-V, I-III and III-V intervals at all 91–910/s clicks. Those diagnosed without BPD manifested only moderate prolongation of I-V and III-V intervals at higher click rates. There were marked differences in MLS BAER between babies with BPD and those without BPD. The babies with BPD manifested significantly longer wave V latency and I-V, I-III, and III-V intervals than those without BPD, particularly at higher click rates. Click rate-dependent changes in the I-V and III-V intervals were significantly increased in BPD babies. These results suggest that while diagnosing BPD the VLBW babies diagnosed with BPD have major brainstem neural impairment, whereas those without BPD have only minor impairment. The major MLS BAER abnormalities in BPD may offer an early biomarker of brainstem neural impairment for BPD.